Autoimmune and neuropsychiatric phenotypes in a Mecp2 transgenic mouse model on C57BL/6 background - Li, Yaxi; Zhang, Shu; Tang, Chenling; Yang, Bowen; Atrooz, Fatin; Ren, Zhifeng; Mohan, Chandra; Salim, Samina; Wu, Tianfu (Frontiers in Immunology, 2024)
Systemic Lupus Erythematosus (SLE) impacts the central nervous system (CNS), leading to severe neurological and psychiatric manifestations known as neuropsychiatric lupus (NPSLE). The complexity and heterogeneity of clinical presentations of NPSLE impede direct investigation of disease etiology in patients. The limitations of existing mouse models developed for NPSLE obstruct a comprehensive understanding of this disease. Hence, the identification of a robust mouse model of NPSLE is desirable. In this study, we conducted phenotyping of C57BL/6 mice transgenic for human Mecp2 (B6.Mecp2 Tg1 ). The results revealed elevated proteinuria and an overall increase in autoantibodies, particularly in female B6.Mecp2 Tg1 mice. Flow cytometry confirmed an increase in CD3 + CD4 + T cells in the transgenic mice, along with activated germinal center cells and activated CD11b + F4/80 + macrophages. Moreover, the transgenic mice displayed reduced locomotor activity, heightened anxiety and depression, and impaired short-term memory. Immunofluorescence analysis revealed IgG deposition and immune cell infiltration in the kidney and brain of transgenic mice, as well as the altered neurogenesis, activated microglia, and compromised blood-brain barrier (BBB). Additionally, we examined various signaling molecules implicated in lupus pathogenesis using western blotting, wherein protein levels of various key signaling molecules were differentially modulated upon MeCP2 overexpression, including GFAP, BDNF, Albumin, NCoR1, mTOR, and NLRP3. Collectively, this work demonstrates that B6.Mecp2 Tg1 mice exhibit lupus-like phenotypes as well as robust CNS dysfunctions, suggesting its utility as a new animal model for NPSLE.